Cangrelor versus Ticagrelor in Patients Treated with Primary Percutaneous Coronary Intervention: Impact on Platelet Activity, Myocardial Microvascular Function and Infarct Size: A Randomized Controlled Trial - Ubaid, Salahaddin; Ford, Thomas J.; Berry, Colin; Murray, Heather M.; Wrigley, Benjamin; Khan, Nazish; Thomas, Mark R.; Armesilla, Angel L.; Townend, Jon N.; Khogali, Saib S.; Munir, Shahzad; Martins, Joe; Hothi, Sandeep S.; McAlindon, Elisa J.; Cotton, James M. (Thrombosis and Haemostasis, 2019)
Background Oral P2Y12 inhibitors take more than 2 hours to achieve full effect in healthy subjects and this action is further delayed in patients with acute myocardial infarction. Intravenous P2Y12 inhibition might lead to more timely and potent anti-platelet effect in the context of emergency primary angioplasty, improving myocardial recovery.Objectives This article compares the efficacy of intravenous cangrelor versus ticagrelor in a ST-elevation myocardial infarction (STEMI) population treated with primary percutaneous coronary intervention (PPCI).Materials and Methods In an open-label, prospective, randomized controlled trial, 100 subjects with STEMI were assigned 1:1 to intravenous cangrelor or oral ticagrelor. The co-primary endpoints were platelet P2Y12 inhibition at infarct vessel balloon inflation time, 4 and 24 hours. Secondary endpoints included indices of coronary microcirculatory function: index of microvascular resistance (IMR), initial infarct size (troponin at 24 hours) and final infarct size at 12 weeks (cardiac magnetic resonance). Secondary endpoints included indices of coronary microcirculatory function (index of microvascular resistance [IMR]), initial infarct size (troponin at 24 hours), final infarct size at 12 weeks (cardiac magnetic resonance), corrected thrombolysis in myocardial infarction (TIMI) frame count, TIMI flow grade, myocardial perfusion grade, and ST-segment resolution (ClinicalTrials.gov NCT02733341).Results P2Y12 inhibition at first balloon inflation time was significantly greater in cangrelor-treated patients (cangrelor P2Y12 reaction unit [PRU] 145.2 ± 50.6 vs. ticagrelor 248.3 ± 55.1). There was no difference in mean PRU at 4 and 24 to 36 hours post-dosing. IMR, final infarct size, angiographic and electrocardiographic measures of reperfusion were all similar between groups.Conclusion Cangrelor produces more potent P2Y12 inhibition at the time of first coronary balloon inflation time compared with ticagrelor. Despite this enhanced P2Y12 inhibition, coronary microvascular function and final infarct size did not differ between groups.
Keywords: anti-platelet; infarct size; microcirculation; myocardial infarction; percutaneous coronary intervention